(untitled) (Singaporean Journal of Business Economics and Management, 2024)
This study explores the contribution of Development Finance Institutions (DFIs) to agricultural sector development in Nigeria. The African Development Bank (AfDB), World Bank, and International Development Association (IDA) were identified as the key DFIs, while agricultural value added was used as the measure for sector development. Data for these variables was gathered from the World Development Indicators (WDI) and analyzed using the error correction mechanism (ECM). The unit root test showed that all variables were non-stationary but became stationary after first differencing, indicating they were integrated of order one. The co-integration test confirmed the existence of a long-run relationship between the variables. The results showed that both the first and second lags of agricultural value added had a negative impact on its current value, while the one-period lag of AfDB loans had a significant positive effect. Specifically, the increase in the lag of AfDB loans resulted in rise in agricultural value added. Additionally, the lagged values of World Bank and IDA loans showed a significant negative impact on agricultural value added. The study recommends that policymakers prioritize AfDB loans for productive sectors, especially agriculture, to support economic development. Similarly, to ensure that DFIs reach more farmers, they must streamline their loan application processes, reduce bureaucracy, and introduce more flexible loan terms. A more efficient disbursement process will increase accessibility and enable farmers to act quickly on opportunities.